Draft Genome Sequences of Two Bison-Type and Two Sheep-Type Strains of Mycobacterium avium subsp. paratuberculosis - Bannantine, John P. (Microbiol Resour Announc, 2021)
Genome sequences of two type B and two type S strains of Mycobacterium avium subsp. paratuberculosis are presented. These strains were isolated in the United States from sheep, bison, and cattle suffering from Johne’s disease. These genomes will increase our understanding of the minor differences that exist among strains of this genetically stable subspecies.